Digital Forest Installation Test in Gallery Space - Auzani Zeda, Mohamed Kassim (2019)
Modern art and the rapid evolution of technology in software and hardware have enabled designers and artists expanding their arts to new dimensions and perspectives. The developing of digital technology become significant in art practice, which creates innovative possibilities of its' ability for endless artistic expression and for artists to create a new experiential aesthetic. As audience interest and demand for modern art are rising, some artists have started to explore the experiential and expressive potential of technology applications in the arts such as projection mapping. Projection mapping, also known as video mapping, is the art of using projection technology to map digital contents onto any physical object or non-flat surface. The idea is to create illusions of images and turn almost any surface into a dynamic video screen - bringing any physical objects to life through digital images. The mixing of both digital content with physical objects within the real space enables the audience to be immersed with the artwork.